THE EFFORTS OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTERISTICS (PAB) TEACHERS IN IMPLEMENTING THE CHARACTER OF LEARNING DISCIPLINE STUDENTS OF SDN GEMBONGAN 1 BANYUSARI KAB. KARAWANG DURING THE COVID-19 PANDEMIC - Karsuhanah (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
Planting and strengthening character education continues even during the pandemic. This situation shows that in this learning emergency it can still be done, it is very positive, but what was found needs an in-depth study, because on the other hand, the problem of distance learning during covid 19 is that parents complain a lot. This study aims to determine the efforts of Islamic Religious Education Teachers and Budi Pekerti in instilling student discipline, the supporting and inhibiting factors in instilling student discipline in SDN Gembongan 1 Banyusari Karawang. The efforts of Islamic Religious Education Teachers and good character are the efforts of teachers inside and outside of learning activities, educating or developing human nature and making them human beings who are faithful, devoted and have noble character according to Islamic teachings. The research focused on 1 elementary school located in the Kab. Karawang, namely at SDN Gembongan 1 Banyusari, using qualitative research, case study methods, a research procedure that produces descriptive data in the form of written or oral data from people and observable behavior as research objects. It is concluded that the efforts of Islamic Religious Education teachers and Budi Pekerti to discipline students include maximizing the role of teachers in intra-curricular and co-curricular activities, namely maximizing lesson planning by disciplining prayer before studying; discipline students during the initial apperception of learning; discipline students through an invitation to concentrate on learning, discipline students through advice and motivation while teaching through an invitation to enthusiastic students in learning. In co-curricular, it is done by giving additional assignments, giving evaluation after learning (Post Test) Home Visit. Supporting factors come internally and externally to the school. Inhibiting factors include minimal facilities, limited teachers, technological stuttering, low student motivation, community economic level and limited school budgets. It is recommended that school principals maintain their role in building and realizing schools that are disciplined and responsible for various programs. Teachers and other stakeholders are expected to support various school programs in building discipline.